Dynamic load balancing in PC clusters: an application to a multiphysics model - Dorneles, R. V.; Rizzi, R. L.; Diverio, T. A.; Navaux, P. O. A. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2003: Anais do XV Symposium on Computer Architecture and High Performance Computing, 2003)
We describe the use of dynamic load balancing in a PC cluster, applied to a multiphysics model that combines the parallel solution for three-dimensional (3D) PDEs of shallow water bodies flow and the parallel solution for the three-dimensional PDEs of scalar transportation of substances. The dynamic load balancing is obtained via diffusion algorithms. The numerical mesh is partitioned using RCB algorithm, in order to minimize communication and balance the load. Parallelism is obtained through Schwarz's additive domain decomposition method (DDM), so that the subproblems are solved concurrently. SPMD is the programming model used and the message passing between processes in the PC cluster is done with MPICH library.